2005
DOI: 10.1111/j.1471-4159.2005.03351.x
|View full text |Cite
|
Sign up to set email alerts
|

Regional and subtype selective changes of neurotransmitter receptor density in a rat transgenic for the Huntington's disease mutation

Abstract: Regional and subtype selective changes of neurotransmitter receptor density in a rat transgenic for the Huntington's disease mutation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 1 publication
1
7
0
Order By: Relevance
“…In the striatum of transgenic mouse or rat models of HD, no changes in benzodiazepine or GABA binding 63,64 or a slight, albeit significant increase 65 have been reported. Functional and molecular analyses of GABAergic neurotransmission in the striatum have revealed complex changes in this brain structure ( Figure 2).…”
Section: Alter Ati On Of G Aba Neurotr Ans Miss Ion In Ms Nsmentioning
confidence: 95%
See 2 more Smart Citations
“…In the striatum of transgenic mouse or rat models of HD, no changes in benzodiazepine or GABA binding 63,64 or a slight, albeit significant increase 65 have been reported. Functional and molecular analyses of GABAergic neurotransmission in the striatum have revealed complex changes in this brain structure ( Figure 2).…”
Section: Alter Ati On Of G Aba Neurotr Ans Miss Ion In Ms Nsmentioning
confidence: 95%
“…Interestingly, quantitative autoradiography has been used to assess neurotransmitter receptor densities in several brain regions in a rat model for the HD mutation. 63 These analyses showed that the expression levels of receptors of the cholinergic, dopaminergic, serotoninergic, noradrenergic, glutamatergic, and GABAergic systems are either increased, decreased, or remain unchanged. These findings in turn suggest that receptor alterations in HD are subtype selective and regionally differential.…”
Section: Alter Ati On Of the G Aba Sys Tem In The Hd B R Ainmentioning
confidence: 99%
See 1 more Smart Citation
“…Reduced levels of serotonin have been found in animal and human HD studies. [9][10][11][12][13][14][15] Treatment trials with selective serotonin reuptake inhibitors (SSRIs) have shown improved symptoms in HD mice, 13,16 yet only 1 randomized controlled trial (RCT) using an SSRI (fluoxetine) in adults with HD has been conducted. 17 The current trial is the first RCT in HD with the primary endpoint of improved executive function.…”
mentioning
confidence: 99%
“…The possibilities include an upregulation of the NMDA receptors in older brains, an increase in Ca 2+ levels due to the release from ER and ⁄ or to mitochondrial dysfunctions. Because some evidence from the literature did not support the hypothesis of the increase in NMDA receptors in HD (Young et al, 1988;von Horsten et al, 2003;Bauer et al, 2005) or in R6 ⁄ 1 and R6 ⁄ 2 mice models (Cha et al, 1998(Cha et al, , 1999NicNiocaill et al, 2001), we investigated the effect of Glu in the absence of external Ca 2+ . In fact, Glu response in these conditions was not significantly different than the response in the presence of external Ca 2+ , indicating that participation of NMDA receptors in this response is more important in transgenic mice.…”
Section: Discussionmentioning
confidence: 99%